O que acontece com a pesquisa quando a arte toma a frente?: potencialidades da pesquisa baseada em arte - Magave, Jade Pena (2014)
What is the role of art within the Academy? How can art be conceived as something beyond a contemplative object and become an active base for research? Such questions, which inquire about the potential of art as a way of knowledge, will give the guide lines to this work on Arts-Based Research, allowing us to rethink the role of art in the academic research and, more generally, aiming for a deeper understanding of art as a way of thought. With that in mind, this research addresses questions regarding the relation between art and knowledge and for that it explores the Arts-Based Research field based on the writings of Elliot Eisner and Tom Barone (2012); Joaquin Roldan and Ricardo Marin Viadel (2012). The Arts-Based Research is also analyzed in a case study: six papers presented during the 1st Conference on Arts-based Research and Artistic Research held in Barcelona in 2012. Furthermore, this work includes some visual and verbal narratives, expanding the reflection and analysis of the potential use of art in research, as well as emphasizing the importance of creation processes in the construction of knowledge in academic research.